Soft Skills and Their Role in the Quality of Accounting Profits: An Exploratory Study of the Opinions of a Sample of Accountants of Industrial Companies in Nineveh Governorate - Anfal Saber Sharif; Ola Majid Basheer; Bakr Ayoob Saleh (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
The research aims to examine the relationship and impact between soft skills (independent variable) and the quality of accounting profits (dependent variable) by surveying the opinions of accountants in several industrial companies in Nineveh Province. To achieve this goal, a questionnaire was distributed to a randomly selected sample of 31 respondents. The research employed a descriptive-analytical methodology to address the research hypotheses and derive conclusions. The study reached several key conclusions, notably that soft skills enhance creativity, innovation, organizational abilities, and problem-solving capabilities within organizations. These skills and attributes are crucial for addressing complex tasks within the organization to ensure both individual and organizational success in a dynamic environment. The research also provided several recommendations, including the assertion that relying on soft skills contributes to the quality of accounting profits. This is achieved by producing reports that include adequate information on cost management for sustainable development, adherence to environmental regulations, effective investment planning, optimal resource and energy utilization, and waste management and reporting to stakeholders and the community.